IDENTIFIKASI DAN HABITAT GURITA (CEPHALOPODA) DARI PERAIRAN SALIBABU, KABUPATEN KEPULAUAN TALAUD - Andika R Balansada; Medy Ompi; Frans Lumoindong (Sam Ratulangi University, 2019)
The octopus in Manado language is called Boboca, while the local Talaud community is called Urrita. Octopus is used as food and bait. Information on octopus biology needs to be known as basic information in the management of octopus resources. This study aims to identify and provide information on octopus habitat in the waters of Salibabu. Collecting specimens using arrows (jubi). The morphology of the example octopus is identified as Octopus cyanea Gray, 1849. In the arms of the octopus there are white-colored spots. On the left and right side of the crown of the arm are two false eyes (ocellus). On the face of the ventral arm is a dark pole pattern above the pale or creamy base color. Characteristics of female morphomes generally have a larger size compared to males. Specimen habitats are found outside the nest at night and in the nest during the day time.Keywoeds: Octopus, Biology, Identify, Morphology, Morphometric, Habitat